Pengaruh Flexible Working Arrangement terhadap Work Engagement pada Karyawan Milenial Perusahaan Startup Digital di Kota Bandung - Reskina Winialda; Yuli Aslamawati (Bandung Conference Series: Psychology Science, 2023)
Abstract. This study aims to empirically examine the effect of flexible working arrangement on millennial employees work engagement in digital startup companies in Bandung City. This research used a quantitative approach with a cross-sectional survey design. This study used non-probability sampling, specifically convenience/ accidental sampling, with a sample size of 120 employees. Measurment scale using the Flexible Working Arrangement Scale from Farida and Utrecht Work Engagement Scale-17 (UWES-17) from Wilmar Schaufeli. The data analysis technique to test the research hypothesis used a multiple regression technique test. The results of this research shows that 76% millennial employees in digital startup companies in Bandung City have a high level of flexible working arrangement and 96% have a high level of work engagement. Simultaneously, flexible working arrangements have an 8.5% influence on work engagement. However, only one dimension of flexible working arrangements, that is flexible location, significantly affects work engagement. The other dimension, flexible time, does not have a significant impact on work engagement. The implication of this research is the importance of implementing flexible working arrangements, particularly in the dimension of flexible location, to enhance millennial employees work engagement in digital startup companies. Abstrak. Penelitian ini bertujuan untuk menguji secara empiris pengaruh flexible working arrangement terhadap work engagement karyawan milenial perusahaan startup digital di Kota Bandung. Pendekatan yang digunakan ialah kuantitatif dengan desain cross-sectional survey. Teknik pengambilan sampel dalam penelitian ini menggunakan non-probability sampling yaitu convenience/ accidental sampling, dengan jumlah sampel sebanyak 120 orang. Alat ukur yang digunakan adalah skala Flexible Working Arrangement dari Farida dan Utrecht Work Engagement Scale-17 (UWES-17) dari Wilmar Schaufeli, analisis data menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa 76% karyawan milenial perusahaan startup digital di Kota Bandung memiliki flexible working arrangement yang tinggi dan 96% karyawan milenial perusahaan startup digital di Kota Bandung memiliki work engagement yang tinggi. Secara simultan, flexible working arrangement berpengaruh terhadap work engagement sebesar 8.5%. Sedangkan secara parsial hanya satu dimensi flexible working arrangement yaitu flexible location berpengaruh secara signifikan terhadap work engagement. Sementara dimensi lainnya yaitu flexible time tidak berpengaruh secara signifikan terhadap work engagement. Implikasi penelitian ini adalah pentingnya penerapan flexible working arrangement terutama pada dimensi flexible location dalam meningkatkan work engagement karyawan milenial perusahaan startup digital.